The Role of the East Java Department of Industry and Trade in Promoting the Creative Industry in Society through Jatim Information Technology Creative Surabaya - Masitha Rizki Rahayu; , Muchammad Ismail (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This research discusses the strategic role of the East Java Province Department of Industry and Trade in developing creative industries through the establishment and management of the East Java Information Technology Creative (JITC) Surabaya. The background to the formation of JITC is based on the increasing importance of the creative and digital industry sector in driving regional economic growth and job creation in the era of a knowledge-based economy. The East Java Provincial Government responded to this development by providing technology facilities and collaboration spaces that support the activities of creative industry players, especially digital startups. JITC not only functions as a center for innovation and human resource training, but also as an ecosystem that facilitates digital product development, technical skills training, and expanding market networks for creative business actors. Apart from that, JITC's contribution to local revenue (PAD) is also starting to be seen through increasing local economic activity, business taxes, and the creation of new technology-based businesses. This research uses a qualitative approach with a case study method which focuses on the role of East Java Information Technology Creative (JITC) Surabaya as the main unit of analysis. This research shows that collaboration between government institutions and creative communities through infrastructure such as JITC has a real impact on economic development and sustainable community empowerment.